THE TI-RICH GABBROIC INTRUSIONS OF THE VOLYN MEGABLOCK OF THE UKRAINIAN SHIELD - MYTROKHINA, T.; MYTROKHIN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The characteristic of Ti-rich gabbroic intrusions of the Volyn megablock of the Ukrainian Shield is given in the article. Some petrogenetic conditions of the Ti-rich intrusion formation are determined on the base of generalization of the data about features of their locating, occurrence, structure , age and composition.